Multiferroic behaviour of bismuth ferrite porous thin films - Skiadopoulou, Styliani (2018)
An enormous contribution in the scientific community of material engineering is being made by the exceptionally rapid evolution of the field of multifunctional materials. Multiferroics combine simultaneously at least two of the three ferroic properties: ferroelectricity, ferromagnetism and ferroelasticity. Magnetoelectric multiferroics’ ability of magnetic field manipulation via electric fields or vice versa can be extremely promising for information storage applications, leading to thinner, as well as flexible devices, with significantly high energetic efficiencies and elevated capacities. The aim of this work is the preparation and characterization of bismuth ferrite porous thin films, having as further objective to be able to serve as matrices for future functionalization. The strategy of this work consists of: a) dense film preparation with varying deposition velocities, b) porous film preparation with varying solution template quantities, inorganic precursor concentration and deposition velocities. Annealing temperature studies were also required, for the obtainment of the desired properties and control of microstructure. The methodologies for the film preparation in use were: a) sol-gel process, b) Evaporation Induced Self-Assembly (EISA), for the induction of porosity, and c) dip-coating technique. A series of dense films with varying deposition velocities were produced, serving as means of comparison for the porous thin films. Increasing the sol-gel deposition velocity led to increasing thickness. Piezoresponse Force Microscopy (PFM) characterization was conducted, revealing the expected ferroelectric domains. By the same technique, local piezoelectric hysteresis loops were obtained, showing increase of polarization saturation with increasing thickness. Lastly, magnetic moment measurements were carried out by the use of Superconducting Quantum Interference Device (SQUID), presenting decrease of remnant magnetization with increasing thickness. Varying template concentration was introduced in order to obtain a homogenous porous network. Homogeneity and lack of cracks in the films were successfully achieved, by decreasing solution template mass, for a given solution concentration. Thermal treatment studies revealed loss of porous network ordering at elevated annealing temperatures, required for the obtainment of crystallization and enhanced multiferroic properties. Local piezoelectric hysteresis loops showed increase of the effective piezoelectric coefficient with increasing thickness. SQUID characterization presented increasing remnant magnetization with increasing porosity. Lastly, increasing inorganic precursors concentration resulted in better control of porosity order and increase in the piezoelectric coefficient.